Plasma Selenium Concentrations Are Sufficient and Associated with Protease Inhibitor Use in Treated HIV-Infected Adults. Issue 10 (12th August 2015) - Hileman, Corrilynn O; Dirajlal-Fargo, Sahera; Lam, Suet Kam; Kumar, Jessica; Lacher, Craig; Combs, Gerald F; McComsey, Grace A
Abstract: Background: Selenium is an essential constituent of selenoproteins, which play a substantial role in antioxidant defense and inflammatory cascades. Selenium deficiency is associated with disease states characterized by inflammation, including cardiovascular disease (CVD). Although HIV infection has been associated with low selenium, the role of selenium status in HIV-related CVD is unclear. Objectives: We sought to assess associations between plasma selenium and markers of inflammation, immune activation, and subclinical vascular disease in HIV-infected adults on contemporary antiretroviral therapy (ART) and to determine if statin therapy modifies selenium status. Methods: In the Stopping Atherosclerosis and Treating Unhealthy bone with RosuvastatiN trial, HIV-infected adults on stable ART were randomly assigned 1:1 to rosuvastatin or placebo. Plasma selenium concentrations were determined at entry, week 24, and week 48. Spearman correlation and linear regression analyses were used to assess relations between baseline selenium, HIV-related factors and markers of inflammation, immune activation, and subclinical vascular disease. Changes in selenium over 24 and 48 wk were compared between groups. Results: One hundred forty-seven HIV-infected adults were included. All participants were on ART. Median current CD4+ count was 613, and 76% had HIV-1 RNA ≤48 copies/mL (range: <20–600). Median plasma selenium concentration was 122 μg/L (range: 62–200). At baseline, higher selenium was associated with protease inhibitor (PI) use, lower body mass index, and a higher proportion of activated CD8+ T cells (CD8+CD38+human leukocyte antigen-DR+), but not markers of inflammation or subclinical vascular disease. Over 48 wk, selenium concentrations increased in the statin group ( P < 0.01 within group), but the change did not differ between groups (+13.1 vs. +5.3 μg/L; P = 0.14 between groups). Conclusions: Plasma selenium concentrations were within the normal range for the background population and were not associated with subclinical vascular disease in HIV-infected adults on contemporary ART. The association between current PI use and higher selenium may have implications for ART allocation, especially in resource-limited countries. Also, it appears that statin therapy may increase selenium concentrations; however, larger studies are necessary to confirm this finding. This trial was registered at clinicaltrials.gov as NCT01218802.